Analysis Of The Decision Of The Karawang Religious Court Number 555/Pdt. G/2024/Pa. Krw On The Determination Of Joint Property In Polygamy Permit Cases To Prevent Family Conflicts - Rafly, Muhammad; Farhan Asyhadi,; Muhamad Abas, (MIZAN: JOURNAL OF ISLAMIC LAW, 2025)
The allocation of joint assets in polygamous unions involves distinct complexities that necessitate well-defined legal provisions to avert potential conflicts within the family. This research analyzes how legal rules governing joint property in polygamous marriages are implemented, as illustrated in Decision No. 555/Pdt.G/2024/PA.Krw. Utilizing a normative juridical approach combined with a case study method, the study incorporates qualitative analysis of judicial decisions, statutory law, and pertinent legal doctrines. The results reveal that the panel of judges relied on Article 35 of Law No. 1 of 1974 and Article 94 of the Compilation of Islamic Law, both of which mandate that joint property be divided separately for each marital relationship. This measure is intended to ensure legal certainty, safeguard the ownership rights of the first wife, and prevent future disputes. Judicial considerations also included the explicit consent of the first wife and sufficient financial capability of the applicant as prerequisites for granting polygamy. The study concludes that separating joint property in polygamous marriages serves as a preventive legal protection for wives while embodying the principles of justice and legal certainty within the religious court system. Keywords: Marriage; Common Property; Polygamy; Joint Assets